Battery packaging material

By using an adhesive composition of polyester polyurethane acrylate and isobornyl (meth)acrylate monomer, and adding auxiliary ingredients such as epoxy resin, the problem of delamination of battery packaging materials at high temperatures is solved. Higher bonding strength and heat resistance.

CN119343811APending Publication Date: 2025-01-21LISSENOK PACKAGING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380046022.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-28
Filing Date
2023-07-24
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing packaging materials for batteries are prone to delamination between the metal foil and the heat-resistant resin layer under high temperature and harsh conditions, which affects the sealing and service life.

Method used

An adhesive composition containing polyester polyurethane acrylate and a (meth)acrylate monomer with an isobornyl group is used, cured in a short time by electron beam curing, and epoxy resin is added to the adhesive layer , a radically polymerizable compound containing an alkoxysilyl group, a (meth)acrylate containing a phosphate group, and a photocationic polymerization initiator to improve bonding strength and heat resistance.

Benefits of technology

It significantly improves the adhesion strength at high temperature conditions, prevents the layers of metal foil and heat -resistant resin layer, and enhances the sealing and durability of the battery shell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119343811A_ABST
    Figure CN119343811A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to improve the adhesive strength at high temperatures in a battery packaging material using an active energy-curable adhesive. A battery packaging material (1) in which a heat-resistant resin layer (13) is bonded to one surface of a barrier layer (11) via a first adhesive layer (12), and a sealant layer (15) is bonded to the other surface of the barrier layer (11) via a second adhesive layer (14), the first adhesive layer (12) is composed of an adhesive composition containing a polyester urethane acrylate (A) and a (meth) acrylate monomer (B) having an isobornyl group at a mass ratio of (A) / (B) = 1 / 1 to 8 / 1.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a battery packaging material suitable for use as a casing of a secondary battery, particularly a small portable lithium ion secondary battery, for example, for vehicle-mounted, stationary, notebook computer, mobile phone, or camera, and related technology. Background Art

[0002] Electric storage devices such as lithium-ion secondary batteries can be processed into various shapes and made thinner and lighter by using a laminated packaging material made by laminating resin layers on both sides of a metal foil such as aluminum for cans and cases.

[0003] Laminated battery packaging materials are known in which a heat-resistant resin layer film forming the outer surface of a case is bonded to one surface of a metal foil with an adhesive, and a sealant layer resin film is bonded to the other surface with an adhesive, and various adhesives are used.

[0004] In conventional battery packaging materials, a two-component curable urethane adhesive is usually used for laminating a metal foil and a resin film for a heat-resistant resin layer, but there are problems such as poor productivity due to a heat aging process that requires 7 to 9 days for curing, and a large aging room that consumes equipment costs. Therefore, a battery packaging material is proposed that uses an electron beam curable adhesive instead of a two-component curable urethane adhesive, thereby eliminating the need for a heat aging process, greatly shortening the curing time, and eliminating the need for large equipment (see Patent Document 1).

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent No. 5704298 Summary of the invention

[0008] Problems to be solved by the invention

[0009] As for the battery packaging material described in Patent Document 1, the adhesive is cured in a short time by electron beam irradiation, so the productivity is improved. However, if the aforementioned battery packaging material is formed deeper when making the battery shell, there will be a problem that delamination (peeling) is easy to occur between the metal foil and the heat-resistant resin layer that becomes the outer surface of the shell. In addition, there are also the following problems: when the battery shell is sealed with heat sealing, and when the battery is used under harsh conditions such as high temperature and humidity, delamination is easy to occur between the metal foil and the heat-resistant resin layer.

[0010] Means for solving problems

[0011] The present invention has been made in view of the above-mentioned background art, and an object of the present invention is to improve the adhesive strength at high temperatures in a battery packaging material using an electron beam curing adhesive that cures in a short time.

[0012] That is, the present invention has the configurations described in the following [1] to [7].

[0013] [1] A battery packaging material comprising a heat-resistant resin layer laminated to one surface of a barrier layer via a first adhesive layer, and a sealant layer laminated to the other surface via a second adhesive layer, wherein:

[0014] The first adhesive layer is composed of an adhesive composition containing polyester urethane acrylate (A) and an isobornyl-containing (meth)acrylate monomer (B) at a mass ratio of (A) / (B)=1 / 1 to 8 / 1.

[0015] [2] The battery packaging material according to item 1 above, wherein the adhesive composition comprises two or more polyester urethane acrylates (A) having different glass transition temperatures, and the glass transition temperature of at least one polyester urethane acrylate (A) is 40° C. or lower.

[0016] [3] The battery packaging material according to item 1 or 2 above, wherein the adhesive composition further comprises at least one of an epoxy resin (C), a radically polymerizable compound (D) containing an alkoxysilyl group, a (meth)acrylate containing a phosphate group (E), and a photocationic polymerization initiator (F).

[0017] [4] The battery packaging material according to item 1 or 2 above, wherein the adhesive composition further comprises at least one of 1% to 10% by mass of an epoxy resin (C), 0.1% to 5% by mass of a radically polymerizable compound (D) containing an alkoxysilyl group, 0.1% to 5% by mass of a (meth)acrylate containing a phosphate group (E), and 0.1% to 5% by mass of a photocationic polymerization initiator (F).

[0018] [5] The battery packaging material according to any one of the above items 1 to 4, wherein a base layer is formed on at least the surface of the barrier layer on the heat-resistant resin layer side.

[0019] [6] A battery case, characterized in that a battery element chamber for accommodating a battery element is formed by abutting the battery packaging materials according to any one of 1 to 5 above so that the sealant layers face inward and heat-sealing the edges.

[0020] [7] A secondary battery characterized in that a battery element is housed in the battery element chamber of the battery case according to the above item 6.

[0021] Effects of the Invention

[0022] In the battery packaging material described in [1] above, since the first adhesive layer for bonding the barrier layer and the heat-resistant resin layer is composed of an adhesive composition in which a polyester urethane acrylate (A) and a (meth)acrylate monomer (B) having an isobornyl group are blended in a predetermined ratio, it can be cured in a short time by irradiation with active energy rays and has excellent adhesiveness and heat resistance. Therefore, delamination between the barrier layer and the heat-resistant resin layer can be prevented during heat sealing when sealing the battery case or during use of the battery in a high temperature environment.

[0023] According to the battery packaging material described in [2] above, the adhesive composition contains two or more polyester urethane acrylates (A) having different glass transition temperatures, and the glass transition temperature of at least one polyester urethane acrylate is 40° C. or lower, so that both the adhesiveness and heat resistance of the first adhesive layer can be achieved.

[0024] According to the battery packaging material described in [3] or [4] above, the heat resistance is further improved or the adhesiveness is improved.

[0025] According to the battery packaging material described in [5], the adhesion between the barrier layer and the heat-resistant resin layer is improved by the base layer, and the effect of preventing delamination is improved.

[0026] Since the battery case described in [6] is made of the battery packaging material described in [1], delamination during heat sealing can be prevented.

[0027] Since the battery described in [7] above uses the battery case described in [6] above, delamination during use in a high-temperature environment can be prevented. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] [ Figure 1 ] Figure 1 This is a cross-sectional view showing an example of the battery packaging material of the present invention.

[0029] [ Figure 2 ] Figure 2 This is a cross-sectional view showing another example of the battery packaging material of the present invention.

[0030] [ Figure 3 ] Figure 3 Reason Figure 1 A cross-sectional view of a battery case made of a battery packaging material. DETAILED DESCRIPTION

[0031] Figure 1 One embodiment of the battery packaging material of the present invention is shown.

[0032] The battery packaging material 1 includes a heat-resistant resin layer 13 bonded to one surface of a barrier layer 11 via a first adhesive layer 12 , and a sealant layer 15 bonded to the other surface via a second adhesive layer 14 .

[0033] like Figure 3 As shown, the battery case 50 is manufactured by heat-sealing the edges of a molded container 51 and a cover plate 52 using the battery packaging material 1 so that the respective sealant layers 15 are aligned with each other. In addition, the battery 60 is formed by sealing a battery element 55 in the battery element chamber 54 of the battery case 50. In the manufactured battery case 50, the heat-resistant resin layer 13 becomes the outer layer, and the sealant layer 15 becomes the inner layer. In the present invention, when the position of each layer constituting the battery packaging material 1 is described in terms of direction, the direction of the heat-resistant resin layer 13 is referred to as the outer side, and the sealant layer 15 is referred to as the inner side.

[0034] The present invention defines the adhesive composition constituting the first adhesive layer 12 between the barrier layer 11 and the heat-resistant resin layer 13 of the battery packaging material 1 .

[0035] [Main components of the first adhesive layer]

[0036] The adhesive composition constituting the first adhesive layer 1 requires that the polyester urethane acrylate (A) and the (meth)acrylate monomer (B) having an isobornyl group are contained in a mass ratio of (A) / (B)=1 / 1 to 8 / 1. The adhesive composition is cured by irradiation with active energy to firmly bond the barrier layer 11 to the heat-resistant resin layer 13.

[0037] As for the aforementioned polyester polyurethane acrylate (A), the number of functional groups of the acryloyl group in its molecule is not particularly limited, and from the viewpoint of adhesion between substrates, it is preferably 2 or more, and more preferably 2 to 4. When the number of acryloyl groups is less than 2, the crosslinking density after curing is low, so the adhesion and heat resistance are weakened, and the practicality is reduced. When the number of functional groups of the (meth)acryloyl group is greater than 4, the crosslinking density is high, so the adhesion is weakened. In addition, the number average molecular weight is not particularly limited, and is preferably in the range of 4000 to 30000. When the number average molecular weight is less than 4000, the molecular weight between the crosslinking points is low, so the flexibility is impaired and the adhesion is weakened. When the number average molecular weight is greater than 30000, the viscosity is high, the coating adaptability is reduced, and it is therefore not practical. In addition, due to the high molecular weight between the crosslinking points, it becomes too soft after curing and the adhesion is weakened. The number average molecular weight in the present invention is measured by gel permeation chromatography (GPC).

[0038] The (meth)acrylate monomer (B) having an isobornyl group has an effect of improving the heat resistance of the cured film of the active energy curable adhesive composition by reducing the atomic vibration freedom due to its ring structure and preventing molecular motion. The delamination of the barrier layer 11 and the heat resistant resin layer 13 is prevented by improving the heat resistance of the first adhesive layer 12. Examples of the (meth)acrylate monomer (B) having an isobornyl group include isobornyl acrylate and isobornyl methacrylate.

[0039] The aforementioned polyester polyurethane acrylate (A) and the (meth)acrylate monomer (B) having an isobornyl group are mixed in a mass ratio of (A) / (B)=1 / 1 to 8 / 1, thereby forming an adhesive composition having excellent adhesion and heat resistance. If the polyester polyurethane acrylate (A) is less than (A) / (B)=1 / 1, the flexibility of the cured film decreases and the adhesion becomes weak. If the polyester polyurethane (meth)acrylate (A) is more than (A) / (B)=8 / 1, the cured film becomes too soft and the heat resistance becomes weak. The preferred (A) / (B) is 1 / 1 to 6 / 1.

[0040] The polyester urethane acrylate (A) does not need to be one type, and two or more different types may be mixed and used. When two or more types are used, it is preferred that at least one type is a polyester urethane acrylate (A) having a glass transition temperature (Tg) of 40°C or less. By using a polyester urethane acrylate (A) having a low glass transition temperature (Tg), adhesion and heat resistance can be achieved at the same time.

[0041] When two or more types are used, all types may be polyester urethane acrylates (A) having a glass transition temperature (Tg) of 40°C or less, or polyester urethane acrylates (A) having a glass transition temperature (Tg) of more than 40°C may be used together with polyester urethane acrylates (A) having a glass transition temperature (Tg) of 40°C or less.

[0042] In the following description, polyester urethane acrylate (A) having a glass transition temperature (Tg) of 40°C or less is referred to as polyester urethane acrylate (A1), and polyester urethane acrylate (A) having a glass transition temperature (Tg) of more than 40°C is referred to as polyester urethane acrylate (A2).

[0043] When polyester urethane acrylate (A1) and polyester urethane acrylate (A2) are used in combination, the amount of polyester urethane acrylate (A2) is preferably 75 parts by mass or less relative to 100 parts by mass of polyester urethane acrylate (A1). If the amount of polyester urethane acrylate (A2) exceeds 75 parts by mass, the flexibility of the cured first adhesive layer 12 decreases, and the adhesion between the barrier layer 11 and the heat-resistant resin layer 13 may decrease. The particularly preferred amount of polyester urethane acrylate (A2) is 20 to 60 parts by mass relative to 100 parts by mass of polyester urethane acrylate (A1).

[0044] The polyester urethane acrylate (A) can be obtained by reacting a polyester polyol (a-1) as a polyol component with an isocyanate compound (a-2) and a (meth) hydroxy acrylate (a-3). The following starting materials and synthesis methods are common regardless of the glass transition temperature (Tg).

[0045] The polyester polyol (a-1) may be prepared by mixing a polybasic acid component such as isophthalic acid, terephthalic acid, naphthalene dicarboxylic acid, phthalic anhydride, succinic acid, adipic acid, azelaic acid, sebacic acid, maleic acid, fumaric acid, itaconic acid, anhydrides thereof, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, tetrabromophthalic anhydride, tetrachlorophthalic anhydride, chlorophthalic anhydride, nadic anhydride, etc., alone or in mixture, with a polybasic acid component such as ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, neopentyl glycol, triethylene glycol, tripropylene glycol, etc. It is obtained by dehydrating and condensing a single or a mixture of polyol components such as glycol, tetramethylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene ether glycol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,9-nonanediol, 2-methyl-1,8-octanediol, hydrogenated bisphenol A, glycerol, trimethylolethane, trimethylolpropane, trihydroxymethylaminomethane, pentaerythritol, polyether polyol, polycarbonate polyol, acrylic polyol, polyurethane polyol, etc.

[0046] As the polyol component, a polyol other than the polyester polyol (a-1) may be used in combination, for example, low molecular weight polyols such as 1,6-hexanediol and trimethylolpropane, polyether polyols, acrylic polyols, and polyurethane polyols, which may be used alone or in combination of two or more.

[0047] Examples of the isocyanate compound (a-2) include 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 1,3-xylylene diisocyanate, 1,4-xylylene diisocyanate, 1,5-naphthalene diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, 3,3′-dimethylphenylene diisocyanate, 1,6-hexamethylene diisocyanate, isophorone diisocyanate, 4,4′-methylenebis(cyclohexyl isocyanate), 2,2,4- Trimethylhexamethylene diisocyanate, norbornene diisocyanate, etc., and further, as the multifunctional polyisocyanate compound, their biuret body, urate body, and trimethylolpropane adduct can be mentioned, and as the isocyanate compound having a (meth)acryloyl group, (meth)acrylate 2-isocyanatoethyl ester, 2-(2-methacryloyloxyethyloxy)ethyl isocyanate, 1,1-(bisacryloyloxymethyl)ethyl isocyanate can be mentioned, and they can be used alone or in combination of two or more.

[0048] As for the above-mentioned hydroxy (meth)acrylate (a-3), for example, as a compound having one (meth)acryloyl group, there can be mentioned 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 1,5-pentanediol mono(meth)acrylate, 1,6-hexanediol mono(meth)acrylate, cyclohexanedimethanol mono(meth)acrylate, polyether-modified hydroxyethyl (meth)acrylate, caprolactone-modified (meth)acrylate. As compounds having two or more acryloyl groups, trimethylolpropane di(meth)acrylate, trimethylolethane di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol di(meth)acrylate, dipentaerythritol tri(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, 2-hydroxy-3-acryloyloxypropyl (meth)acrylate, etc. can be cited, and these can be used alone or in combination of two or more. In addition, considering the reaction rate during synthesis, it is preferably a compound having a primary hydroxyl group, among which 2-hydroxyethyl (meth)acrylate is particularly preferred.

[0049] The synthesis of the polyester polyurethane acrylate (A) can be carried out in a solvent as needed. As these solvents, for example, hydrocarbons other than alcohols, acetates, ketones, etc. can be cited. From the viewpoint of coating workability, ethyl acetate and methyl ethyl ketone are preferably used. In addition, known reaction accelerators can be used in the synthesis of polyester polyurethane acrylate (A). As reaction accelerators, metal catalysts such as dibutyltin diacetate, dibutyltin dilaurate, dioctyltin dilaurate, and dibutyltin dimaleate, tertiary amines such as 1,8-diazabicyclo (5,4,0) undecene-7 and 1,5-diazabicyclo (4,3,0)-nonene-5, and reactive tertiary amines such as triethanolamine can be cited.

[0050] In the aforementioned adhesive composition, as a component for improving adhesion, a polyisocyanate or an isocyanate compound (X) having a free radical polymerizable unsaturated bond that is not a constituent component of polyester polyurethane acrylate can be added. By adding the isocyanate compound (X), the cohesive force is improved by utilizing the reaction between the hydroxyl group of the adhesive cured product, the moisture attached to the barrier layer 11 and the heat-resistant resin layer 13 as the bonding object, and the isocyanate group, thereby obtaining excellent adhesion. However, if the aforementioned isocyanate compound is added in an amount exceeding 25% by mass, the curing time becomes longer, or carbon dioxide is generated due to the reaction of water such as moisture with the isocyanate, which sometimes generates bubbles in the adhesive layer, so the proportion of the isocyanate compound in the adhesive composition is preferably less than 25% by mass. It should be noted that the aforementioned isocyanate compound (X) shown here is not a constituent component of polyester polyurethane acrylate (A).

[0051] The adhesive composition is cured by irradiation with active energy rays such as ultraviolet rays, X-rays, visible light, α rays, β rays, γ rays, and EB (electron beams), to form the first adhesive 12, and the barrier layer 11 and the heat-resistant resin layer 13 are bonded. The first adhesive layer 12, which is a cured film of the adhesive composition, has high heat resistance, and the bonding strength between the barrier layer 11 and the heat-resistant resin layer 13 is also high at high temperatures, which can prevent delamination during heat sealing.

[0052] [Auxiliary Components in the First Adhesive Layer]

[0053] The adhesive composition may optionally contain at least one of the following auxiliary components (C) to (F) in addition to the above components.

[0054] The epoxy resin (C) is a component that contributes to improving the heat resistance of the first adhesive layer 12 .

[0055] The epoxy resin is a general term for resins having epoxy groups in the molecule and epoxy (meth) acrylates obtained by modifying resins having epoxy groups in the molecule to give (meth) acryloyl groups in the molecule. Specific examples include bisphenol A epoxy resins, bisphenol F epoxy resins, alicyclic epoxy resins, Novolac epoxy resins, epoxy acrylates, and the like. For example, bisphenol A type epoxy resins include those manufactured by Mitsubishi Chemical Corporation (jER825, jER827, jER828, jER1001, jER1002, jER1003, jER1004, jER1032H60), etc., bisphenol F type epoxy resins include those manufactured by Mitsubishi Chemical Corporation (jER4004P, jER4005P), etc., alicyclic epoxy resins include those manufactured by Daicel Corporation (CELLOXIDE 2021P, CELLOXIDE 2081, EPOLEAD GT401), etc., and Novolac type epoxy resins include those manufactured by DIC Corporation (EPICLON N-660, EPICLON N-740) and the like. Examples of epoxy acrylates include EBECRYL 600, EBECRYL 3603, and EBECRYL 3700 manufactured by Daicel Allnex Corporation. These can be used alone or in combination of two or more.

[0056] The content of the epoxy resin (C) in the adhesive composition is preferably 0.1% by mass to 10% by mass. If the content of the epoxy resin (C) exceeds 10% by mass, the adhesiveness may be reduced.

[0057] The radical polymerizable compound (D) containing an alkoxysilyl group is a component that contributes to improving the adhesion to the barrier layer 11, that is, the metal material.

[0058] The above-mentioned radical polymerizable compound (D) containing an alkoxysilyl group is not particularly limited as long as it is a radical polymerizable compound having an alkoxysilyl group in the molecule. For example, vinyl trimethoxysilane, vinyl triethoxysilane, vinyl tributoxysilane, allyl trimethoxysilane, 3-(methyl) acryloxypropyl trimethoxysilane, 3-(methyl) acryloxypropyl triethoxysilane, p-phenylene trimethoxysilane, p-phenylene trimethoxysilane, and organic siloxanes obtained by condensing them alone or two or more thereof can be used alone or in combination of two or more thereof.

[0059] The content of the alkoxysilyl group-containing radically polymerizable compound (D) in the adhesive composition is preferably 0.1% by mass to 5% by mass. If it exceeds 5% by mass, the adhesiveness and heat resistance may be reduced.

[0060] The (meth)acrylate (E) containing a phosphoric acid group contributes to improving the adhesiveness to the barrier layer 11, that is, the metal material.

[0061] The aforementioned (meth)acrylate (E) containing a phosphate group may be used alone or in combination with a phosphorus compound not containing a (meth)acryloyl group, but the (meth)acrylate (E) containing a phosphate group participating in the crosslinking reaction can obtain excellent adhesion and durability, so it is more preferred. As the (meth)acrylate (E) containing a phosphate group, there are 2-(meth)acryloyloxyethyl acid phosphate, bis(2-(meth)acryloyloxyethyl)-acid phosphate, etc., for example, Kyoeisha Chemical Co., Ltd. (Light Ester P-1M, Light Ester P-2M, Light Acrylate P-1A), BASF (Laromer PA9083), which can be used alone or in combination of two or more.

[0062] The content of the phosphoric acid group-containing (meth)acrylate (E) in the adhesive composition is preferably 0.1% by mass to 5% by mass. If it exceeds 5% by mass, the adhesiveness and heat resistance may be reduced.

[0063] The photocationic polymerization initiator (F) is used as a polymerization initiator for the epoxy resin (C) and the alkoxysilyl group-containing radical polymerizable compound (D).

[0064] The photocationic polymerization initiator (F) is an ionic aromatic sulfonium salt-based onium salt, aromatic iodonium salt-based onium salt, etc. formed of a cation part and an anion part, and examples thereof include those manufactured by IGM Resins BV (Omnicat 250, Omnicat 270), manufactured by ADEKA Co., Ltd. (Adeka Optomer SP series), and manufactured by San-Apro Co., Ltd. (CPI-100P, CPI-101A).

[0065] From the viewpoint of reactivity, the content of the photocationic polymerization initiator (F) in the adhesive composition is preferably 0.1% by mass to 5% by mass.

[0066] Furthermore, the adhesive composition may contain coloring pigments, extender pigments, dyes, tackifiers, dispersants, defoamers, wetting agents, antistatic agents, thickeners, antioxidants, ultraviolet absorbers, free radical scavengers, etc., as necessary and within a range that does not impair its performance.

[0067] The adhesive composition is instantaneously cured by irradiation with active energy rays, and a photoradical polymerization initiator may be added to improve curability.

[0068] Examples of the photoradical polymerization initiator include benzophenone, 2,2-dimethoxy-1,2-diphenylethane-1-one, 1-hydroxy-cyclohexyl-phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-propane-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methylpropane-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]-phenyl}-2-methyl-propane-1-one, methyl phenylglyoxylate, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholino Propane-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butane-1-one, 2-dimethylamino-2-(4-methyl-benzyl)-1-(4-morpholin-4-yl-phenyl)-butane-1-one, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, 1,2-octanedione, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-ethanone-1-(O-acetoxime), etc., these can be used alone or in combination of two or more.

[0069] The adhesive composition may be diluted with a solvent such as hydrocarbons, acetates, ketones, alcohols, etc. to adjust the viscosity according to the coating method and the type of the coating machine. From the viewpoint of coating workability, ethyl acetate and methyl ethyl ketone are preferred.

[0070] The adhesive composition may contain a radically polymerizable reactive diluent in accordance with the coating method and the type of the coater in order to adjust the viscosity within a range that does not impair the performance.

[0071] Examples of the reactive diluent include monofunctional (meth)acrylates such as 4-tert-butylcyclohexyl (meth)acrylate, 2-(2-ethoxyethoxy)ethyl (meth)acrylate, stearyl (meth)acrylate, diethylene glycol monobutyl ether (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, lauryl (meth)acrylate, isooctyl (meth)acrylate, tridecyl (meth)acrylate, isobornyl (meth)acrylate, myristyl (meth)acrylate, 1,3-butanediol diacrylate, 1,4- Bifunctional (meth)acrylates such as butanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, and tripropylene glycol di(meth)acrylate, and polyfunctional (meth)acrylates such as trimethylolpropane tri(meth)acrylate, ethoxylated (3) trimethylolpropane tri(meth)acrylate, and propoxylated (3) glycerol tri(meth)acrylate may be used alone or in combination of two or more.

[0072] [Other layers]

[0073] In the battery packaging material of the present invention, known materials can be used as appropriate for the layers other than the first adhesive layer 12, and the lamination method is not particularly limited. Suitable materials for the layers other than the first adhesive layer 12 are described below.

[0074] (Heat-resistant resin layer)

[0075] In the aforementioned heat-resistant resin layer 13, a heat-resistant resin film that does not melt at the heat-sealing temperature when the battery packaging material 1 is heat-sealed is used. As the aforementioned heat-resistant resin, a heat-resistant resin having a melting point that is 10°C or higher, preferably 20°C or higher, than the melting point of the resin constituting the sealant layer 15 is used. As a resin that meets this condition, for example, polyamide films, polyester films, etc. can be cited, and their stretched films are preferably used. Among them, as the aforementioned heat-resistant resin layer 13, biaxially stretched polyester films such as biaxially stretched polyamide films, biaxially stretched polybutylene terephthalate (PBT) films, biaxially stretched polyethylene terephthalate (PET) films, or biaxially stretched polyethylene naphthalate (PEN) films are particularly preferably used. As the aforementioned polyamide film, there is no particular limitation, for example, 6 polyamide films, 6,6 polyamide, MXD polyamide films, etc. can be cited. The heat-resistant resin layer 13 may be formed of a single layer, or may be formed of a multilayer including, for example, a polyester film / polyamide film (a multilayer including a PET film / nylon film, etc.).

[0076] The thickness of the heat-resistant resin layer 13 is preferably 7 μm to 50 μm, which can not only protect against the influence of electrolytes and other chemical resistance, but also ensure sufficient strength as a packaging material, and can reduce the stress during molding such as bulging and drawing, and can improve the moldability. The thickness of the heat-resistant resin layer 13 is more preferably 9 μm to 30 μm.

[0077] A protective layer containing a binder resin and solid particles may be laminated outside the heat-resistant resin layer 13. The protective layer imparts slidability to the surface of the battery packaging material to improve moldability and imparts excellent chemical resistance, solvent resistance, and abrasion resistance.

[0078] (Barrier layer)

[0079] The barrier layer 11 is responsible for imparting gas barrier properties to the battery packaging material 1 to prevent the intrusion of oxygen and moisture. The barrier layer 11 is not particularly limited, and examples thereof include metal foils such as 1000 series, 3000 series, and 8000 series aluminum foils, SUS foils (stainless steel foils), copper foils, nickel foils, titanium foils, and cladding foils. The thickness of the barrier layer 11 is preferably 20 μm to 100 μm. By setting it to 20 μm or more, the generation of pinholes during rolling when manufacturing the metal foil can be prevented, and by setting it to 100 μm or less, the stress during forming such as embossing and drawing can be reduced, and the formability can be improved. The particularly preferred thickness of the barrier layer 11 is 25 μm to 85 μm.

[0080] In addition, it is preferred that the barrier layer 11 has a base layer formed on at least the surface of the barrier layer 11 on the heat-resistant resin layer 13 side. Figure 2 The battery packaging material 2 has base layers 16a and 16b formed on both sides of the barrier layer 11. The base layer 16b on the heat-resistant resin layer 13 side has the effect of improving the adhesion between the barrier layer 11 and the first adhesive layer 12 and improving the bonding strength, and can prevent the barrier layer 11 and the heat-resistant resin layer 13 from being delaminated. The base layer 16b on the sealant layer 15 side can improve the adhesion between the barrier layer 11 and the second adhesive layer 14 to prevent the barrier layer 11 and the sealant layer 15 from being delaminated, and can prevent the corrosion of the metal foil surface caused by the contents (battery electrolyte, etc.) in the battery element chamber 54 of the battery case 60 (see Figure 3 ).

[0081] Examples of the base layers 16a and 16b include chemical conversion films. The chemical conversion film can be formed by subjecting the barrier layer 11 to a chemical conversion treatment as described below.

[0082] The chemical conversion treatment is performed by applying any of the following aqueous solutions 1) to 3) on the surface of the barrier layer 11 that has been subjected to the degreasing treatment, followed by drying.

[0083] 1) An aqueous solution containing a mixture of phosphoric acid, chromic acid, and at least one compound selected from the group consisting of a metal salt of a fluoride and a non-metallic salt of a fluoride

[0084] 2) an aqueous solution containing a mixture of phosphoric acid, at least one resin selected from the group consisting of acrylic resins, chitosan derivative resins and phenolic resins, and at least one compound selected from the group consisting of chromic acid and chromium (III) salts

[0085] 3) an aqueous solution comprising a mixture of phosphoric acid, at least one resin selected from the group consisting of acrylic resins, chitosan derivative resins and phenolic resins, at least one compound selected from the group consisting of chromic acid and chromium (III) salts, and at least one compound selected from the group consisting of metal salts of fluorides and non-metallic salts of fluorides

[0086] The amount of chromium deposited on the base layers 16a and 16b (per surface) is preferably 0.1 mg / m 2 ~50 mg / m 2 , particularly preferably 2 mg / m 2 ~20 mg / m 2 .

[0087] (Sealing agent layer)

[0088] The sealant layer 15 has excellent chemical resistance even against highly corrosive electrolytes and the like, and also plays the role of imparting heat-sealing properties to the battery packaging material 1 .

[0089] The resin constituting the sealant layer 15 is preferably a monolayer or multilayer film of a polyolefin resin such as a propylene resin, preferably an unstretched film. As the aforementioned propylene resin, propylene polymers (homopolymer PP), propylene-ethylene copolymers, propylene-butene copolymers and other propylene-alpha olefin copolymers can be exemplified. The aforementioned propylene-alpha olefin copolymer can be any of a random copolymer and a block copolymer. As a multilayer propylene film, a three-layer film of a propylene random copolymer-propylene block copolymer-propylene random copolymer can be recommended. The aforementioned multilayer film can be produced by coextrusion or the like.

[0090] The thickness of the sealant layer 15 is preferably 20 μm to 100 μm, and more preferably 30 μm to 80 μm. In addition, the ratio of the thickness of each layer of the three-layer coextruded film of the propylene random copolymer-propylene block copolymer-propylene random copolymer is preferably 1 to 3:4 to 8:1 to 3, with the total thickness being 10.

[0091] The sealant layer 15 may contain additives such as lubricants and anti-blocking materials. The lubricant in the sealant layer 15 is not particularly limited, and examples thereof include saturated fatty acid amides, unsaturated fatty acid amides, substituted amides, hydroxymethylamides, saturated fatty acid bisamides, unsaturated fatty acid bisamides, fatty acid ester amides, and aromatic bisamides.

[0092] The saturated fatty acid amide is not particularly limited, and examples thereof include lauric acid amide, palmitic acid amide, stearic acid amide, behenic acid amide, hydroxystearic acid amide, etc. The unsaturated fatty acid amide is not particularly limited, and examples thereof include oleic acid amide, erucic acid amide, etc.

[0093] The substituted amide is not particularly limited, and examples thereof include N-oleyl palmitamide, N-stearyl stearic acid amide, N-stearyl oleic acid amide, N-oleyl stearic acid amide, N-stearyl erucic acid amide, etc. In addition, the hydroxymethylamide is not particularly limited, and examples thereof include hydroxymethyl stearic acid amide, etc.

[0094] The saturated fatty acid bisamides are not particularly limited, and examples thereof include methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, ethylene bisstearic acid amide, ethylene bishydroxystearic acid amide, ethylene bisbehenic acid amide, hexamethylene bisstearic acid amide, hexamethylene bisbehenic acid amide, hexamethylene hydroxystearic acid amide, N,N'-distearyl adipic acid amide, and N,N'-distearyl sebacic acid amide.

[0095] The unsaturated fatty acid bisamide is not particularly limited, and examples thereof include ethylenebisoleic acid amide, ethylenebiserucic acid amide, hexamethylenebisoleic acid amide, and N,N′-dioleyl sebacic acid amide.

[0096] The aforementioned fatty acid ester amide is not particularly limited, and for example, stearyl ethyl stearate can be cited. The aforementioned aromatic bisamide is not particularly limited, and for example, isophthalene bis stearic acid amide, isophthalene bishydroxy stearic acid amide, N,N'-distearyl isophthalic acid amide can be cited. The lubricant concentration is preferably 300ppm to 5000ppm, and more preferably 500ppm to 3000ppm. In addition, it is preferred that 0.1μg / cm 2 ~1.0 μg / cm 2 lubricant.

[0097] The anti-adhesion material is not particularly limited, and examples thereof include silica particles, acrylic resin particles, aluminum silicate particles, etc. The particle size of the anti-adhesion material is preferably in the range of 0.1 μm to 10 μm in terms of average particle size, and more preferably in the range of 1 μm to 5 μm in terms of average particle size. The concentration of the anti-adhesion material is preferably set to 100 ppm to 5000 ppm.

[0098] (Second Adhesive Layer)

[0099] The second adhesive layer 14 is not particularly limited, and for example, an adhesive containing one or more of polyurethane resin, acrylic resin, epoxy resin, polyolefin resin, elastic resin, fluorine resin, and acid-modified polypropylene resin can be recommended. Among them, an adhesive formed of a polyurethane composite resin with an acid-modified polyolefin as a main component is preferred. In addition, the preferred thickness of the second adhesive layer 14 is 2 μm to 5 μm in dry lamination method, etc. In sandwich lamination method, heat lamination method, etc., it is 3 μm to 20 μm.

[0100] In addition, as the second adhesive layer 14 , the same active energy curable adhesive composition as that of the first adhesive layer 12 may be used.

[0101] [Battery case and battery]

[0102] Figure 3 The battery 60 includes a battery case 50 made of the battery packaging material 1 of the present invention.

[0103] The battery case 50 is formed of a molded container 51 and a cover plate 52 , and is manufactured by abutting the respective sealant layers 15 against each other and heat-sealing the edges to form a battery element chamber 54 with the sealant layer 15 as the inner surface.

[0104] The battery 60 is manufactured by housing a battery element 55 including a positive electrode, a negative electrode, a separator, and an electrolyte in the battery element chamber 54 of the battery case 50 .

[0105] The battery case 50 of the battery 60 is made of the battery packaging material 1 , so that the barrier layer 11 and the heat-resistant resin layer 13 will not delaminate when the battery case 50 is heat-sealed or the battery 60 is used in a high-temperature environment.

[0106] Example

[0107] [Production of battery packaging materials]

[0108] By changing the material of the first adhesive layer 12 Figure 1 , 2 Battery packaging materials 1 and 2 having the structures shown.

[0109] (Materials for Adhesive Composition)

[0110] As polyester urethane acrylate (A1) having a glass transition temperature (Tg) of 40° C. or less, the following three compounds α1, α2, and α3 were synthesized.

[0111] (α1)

[0112] Neopentyl glycol (190 g), 1,6-hexanediol (200 g), ethylene glycol (50 g), isophthalic acid (420 g), adipic acid (20 g), and sebacic acid (100 g) were added to a flask equipped with a nitrogen inlet pipe, a stirrer, a distillation column, and a condenser, and dehydration condensation was carried out at an internal temperature of 180 to 200° C. while stirring. After confirming that the resin acid value reached 15 mgKOH / g, dehydration reaction was further carried out at 200 to 240° C. while nitrogen bubbling. After confirming that the resin acid value reached 2 mgKOH / g or less, the internal pressure was reduced to 15 Torr, and the reaction was continued. After confirming that the resin acid value reached 0.1 mgKOH / g or less, a polyester polyol having a number average molecular weight of 4100 and a hydroxyl value of 27.4 mgKOH / g was obtained.

[0113] The obtained polyester polyol was cooled to 20°C, and dibutyltin dilaurate (0.2 g) and toluene diisocyanate (55.4 g) were added and reacted at 80 to 85°C for 6 hours under a nitrogen stream to obtain a urethane prepolymer having isocyanate groups at both terminals.

[0114] 2-Hydroxyethyl acrylate (30.8 g) was added to the obtained urethane prepolymer, and the reaction was carried out at 80-85° C. The reaction was carried out and the absorption of the isocyanate group was confirmed to disappear completely by infrared absorption spectrum, and the synthesis was completed. A polyester polyurethane acrylate with a number average molecular weight of 15,000 and a glass transition temperature (Tg) of -10° C. was obtained.

[0115] (α2)

[0116] Neopentyl glycol (120 g), 1,6-hexanediol (234 g), ethylene glycol (47 g), isophthalic acid (400 g), adipic acid (179 g), and sebacic acid (20 g) were added to a flask equipped with a nitrogen inlet pipe, a stirrer, a distillation column, and a condenser, and dehydration condensation was carried out at an internal temperature of 180 to 200° C. while stirring. After confirming that the resin acid value reached 15 mgKOH / g, dehydration reaction was further carried out at 200 to 240° C. while nitrogen bubbling was performed. After confirming that the resin acid value reached 2 mgKOH / g or less, the internal pressure was reduced to 15 Torr, and the reaction was continued. After confirming that the resin acid value reached 0.1 mgKOH / g or less, a polyester polyol having a number average molecular weight of 4400 and a hydroxyl value of 25.5 mgKOH / g was obtained.

[0117] The obtained polyester polyol was cooled to 20°C, and dibutyltin dilaurate (0.2 g) and toluene diisocyanate (61.5 g) were added and reacted at 80 to 85°C for 6 hours under a nitrogen stream to obtain a urethane prepolymer having isocyanate groups at both terminals.

[0118] 2-Hydroxyethyl acrylate (35.9 g) was added to the obtained urethane prepolymer, and the reaction was carried out at 80-85° C. The reaction was carried out and the absorption of the isocyanate group was confirmed to disappear completely by infrared absorption spectrum, and the synthesis was completed. A polyester polyurethane acrylate with a number average molecular weight of 8000 and a glass transition temperature (Tg) of -20° C. was obtained.

[0119] (α3)

[0120] Neopentyl glycol (160 g), 1,6-hexanediol (210 g), ethylene glycol (50 g), isophthalic acid (405 g), adipic acid (100 g), and sebacic acid (65 g) were added to a flask equipped with a nitrogen inlet pipe, a stirrer, a distillation column, and a condenser, and dehydration condensation was performed at an internal temperature of 180 to 200° C. while stirring. After confirming that the resin acid value reached 15 mgKOH / g, dehydration reaction was further performed at 200 to 240° C. while nitrogen bubbling. After confirming that the resin acid value reached 2 mgKOH / g or less, the internal pressure was reduced to 15 Torr, and the reaction was continued. After confirming that the resin acid value reached 0.1 mgKOH / g or less, a polyester polyol having a number average molecular weight of 4350 and a hydroxyl value of 26.3 mgKOH / g was obtained.

[0121] The obtained polyester polyol was cooled to 20°C, and dibutyltin dilaurate (0.2 g) and toluene diisocyanate (56.1 g) were added and reacted at 80 to 85°C for 6 hours under a nitrogen stream to obtain a urethane prepolymer having isocyanate groups at both ends.

[0122] 2-Hydroxyethyl acrylate (32.5 g) was added to the obtained urethane prepolymer, and the reaction was carried out at 80-85° C. The reaction was carried out and the absorption of the isocyanate group was confirmed to disappear completely by infrared absorption spectrum, and the synthesis was completed. A polyester polyurethane acrylate with a number average molecular weight of 11,000 and a glass transition temperature (Tg) of -13° C. was obtained.

[0123] As polyester urethane acrylate (A2) having a glass transition temperature of more than 40° C., the following four compounds α11, α12, α13, and α14 were synthesized.

[0124] (α11)

[0125] Neopentyl glycol (130 g), 1,6-hexanediol (180 g), ethylene glycol (80 g), isophthalic acid (310 g), and terephthalic acid (300 g) were added to a flask equipped with a nitrogen inlet pipe, a stirrer, a distillation tower, and a condenser, and dehydration condensation was carried out at an internal temperature of 180 to 200° C. while stirring. After confirming that the resin acid value reached 15 mgKOH / g, dehydration reaction was further carried out at 200 to 240° C. while nitrogen bubbling was performed. After confirming that the resin acid value reached 2 mgKOH / g or less, the internal pressure was reduced to 15 Torr, and the reaction was continued. After confirming that the resin acid value reached 0.1 mgKOH / g or less, a polyester polyol having a number average molecular weight of 5800 and a hydroxyl value of 19.3 mgKOH / g was obtained.

[0126] The obtained polyester polyol was cooled to 20°C, and dibutyltin dilaurate (0.2 g) and toluene diisocyanate (38.5 g) were added and reacted at 80 to 85°C for 6 hours under a nitrogen stream to obtain a urethane prepolymer having isocyanate groups at both terminals.

[0127] 2-Hydroxyethyl acrylate (20.0 g) was added to the obtained urethane prepolymer, and the reaction was carried out at 80-85° C. The reaction was carried out and the absorption of the isocyanate group was confirmed to disappear completely by infrared absorption spectrum, and the synthesis was completed. A polyester polyurethane acrylate with a number average molecular weight of 6000 and a glass transition temperature (Tg) of 50° C. was obtained.

[0128] (α12)

[0129] Neopentyl glycol (130 g), 1,6-hexanediol (177 g), ethylene glycol (82 g), isophthalic acid (310 g), and terephthalic acid (301 g) were added to a flask equipped with a nitrogen inlet pipe, a stirrer, a distillation column, and a condenser, and dehydration condensation was carried out at an internal temperature of 180 to 200° C. while stirring. After confirming that the resin acid value reached 15 mgKOH / g, dehydration reaction was further carried out at 200 to 240° C. while nitrogen bubbling was performed. After confirming that the resin acid value reached 2 mgKOH / g or less, the internal pressure was reduced to 15 Torr, and the reaction was continued. It was confirmed that the resin acid value reached 0.1 mgKOH / g or less, and a polyester polyol having a number average molecular weight of 5820 and a hydroxyl value of 19.2 mgKOH / g was obtained.

[0130] The obtained polyester polyol was cooled to 20°C, and dibutyltin dilaurate (0.2 g) and toluene diisocyanate (38.4 g) were added and reacted at 80 to 85°C for 6 hours under a nitrogen stream to obtain a urethane prepolymer having isocyanate groups at both terminals.

[0131] 2-Hydroxyethyl acrylate (19.3 g) was added to the obtained urethane prepolymer, and the reaction was carried out at 80-85° C. The reaction was carried out and the absorption of the isocyanate group was confirmed to disappear completely by infrared absorption spectrum, and the synthesis was completed. A polyester polyurethane acrylate with a number average molecular weight of 6230 and a glass transition temperature (Tg) of 51° C. was obtained.

[0132] (α13)

[0133] Neopentyl glycol (130 g), 1,6-hexanediol (173 g), ethylene glycol (85 g), isophthalic acid (310 g), and terephthalic acid (302 g) were added to a flask equipped with a nitrogen inlet pipe, a stirrer, a distillation tower, and a condenser, and dehydration condensation was carried out at an internal temperature of 180 to 200° C. while stirring. After confirming that the resin acid value reached 15 mgKOH / g, dehydration reaction was further carried out at 200 to 240° C. while nitrogen bubbling was performed. After confirming that the resin acid value reached 2 mgKOH / g or less, the internal pressure was reduced to 15 Torr, and the reaction was continued. After confirming that the resin acid value reached 0.1 mgKOH / g or less, a polyester polyol having a number average molecular weight of 5850 and a hydroxyl value of 19.1 mgKOH / g was obtained.

[0134] The obtained polyester polyol was cooled to 20°C, dibutyltin dilaurate (0.2 g) and toluene diisocyanate (38.2 g) were added, and reacted at 80 to 85°C for 6 hours under a nitrogen stream to obtain a urethane prepolymer having isocyanate groups at both terminals.

[0135] 2-Hydroxyethyl acrylate (18.7 g) was added to the obtained urethane prepolymer, and the reaction was carried out at 80-85° C. The reaction was carried out and the absorption of the isocyanate group was confirmed to disappear completely by infrared absorption spectrum, and the synthesis was completed. A polyester polyurethane acrylate with a number average molecular weight of 6460 and a glass transition temperature (Tg) of 52° C. was obtained.

[0136] (α14)

[0137] Neopentyl glycol (130 g), 1,6-hexanediol (168 g), ethylene glycol (89 g), isophthalic acid (310 g), and terephthalic acid (303 g) were added to a flask equipped with a nitrogen inlet pipe, a stirrer, a distillation tower, and a condenser, and dehydration condensation was carried out at an internal temperature of 180 to 200° C. while stirring. After confirming that the resin acid value reached 15 mgKOH / g, dehydration reaction was further carried out at 200 to 240° C. while nitrogen bubbling. After confirming that the resin acid value reached 2 mgKOH / g or less, the internal pressure was reduced to 15 Torr, and the reaction was continued. After confirming that the resin acid value reached 0.1 mgKOH / g or less, a polyester polyol having a number average molecular weight of 5890 and a hydroxyl value of 19.0 mgKOH / g was obtained.

[0138] The obtained polyester polyol was cooled to 20°C, and dibutyltin dilaurate (0.2 g) and toluene diisocyanate (37.9 g) were added and reacted at 80 to 85°C for 6 hours under a nitrogen stream to obtain a urethane prepolymer having isocyanate groups at both terminals.

[0139] 2-Hydroxyethyl acrylate (17.4 g) was added to the obtained urethane prepolymer, and the reaction was carried out at 80-85° C. The reaction was carried out and the absorption of the isocyanate group was confirmed to disappear completely by infrared absorption spectrum, and the synthesis was completed. A polyester polyurethane acrylate with a number average molecular weight of 6920 and a glass transition temperature (Tg) of 54° C. was obtained.

[0140] As the (meth)acrylate monomer (B) having an isobornyl group, isobornyl acrylate (Light Acrylate IB-XA manufactured by Kyoeisha Chemical Co., Ltd., glass transition temperature of the homopolymer: 94° C.) was used.

[0141] As the isocyanate compound (X) which is not a constituent component of the polyester urethane acrylate (A1) (A2), TAKENATE D170N manufactured by Takeda Pharmaceutical Company, Ltd. was used.

[0142] As the epoxy resin (C), jER1032H60 manufactured by Mitsubishi Chemical Corporation was used.

[0143] As the alkoxysilyl group-containing radical polymerizable compound (D), X-40-9296 manufactured by Shin-Etsu Chemical Co., Ltd. was used.

[0144] As the (meth)acrylate (E) containing a phosphoric acid group, LightEster P-2M (2-methacryloyloxyethyl acid phosphate) manufactured by Kyoeisha Chemical Co., Ltd. was used.

[0145] As a photocationic polymerization initiator (F), Omnicat 250 manufactured by GM Resins BV was used.

[0146] The above materials were blended to prepare adhesive compositions of Examples 1 to 17 and Comparative Examples 1 to 4. Table 1 shows the types of (A1) and (A2) used in each example and the ratio of each constituent component.

[0147] (Examples 1 and 18)

[0148] The adhesive composition was prepared by mixing the polyester urethane acrylate (A1) of α1, isobornyl acrylate (B), isocyanate compound (X), and auxiliary agents (C, D, E, F). In this example, the polyester urethane acrylate (A2) was not used.

[0149] (Examples 2 to 4, 6 to 16, Comparative Examples 1 and 2)

[0150] The adhesive composition is prepared by mixing α1 or α2 polyester urethane acrylate (A1), any of α11 to α14 polyester urethane acrylate (A2), isobornyl acrylate (B), and auxiliary agents (C, D, E, F). In this example, no isocyanate compound (X) is used.

[0151] (Example 5)

[0152] The adhesive composition was prepared by mixing α1 polyester urethane acrylate (A1), isobornyl acrylate (B), and auxiliary agents (C, D, E, F). In this example, polyester urethane acrylate (A2) and isocyanate compound (X) were not used.

[0153] (Example 17)

[0154] The adhesive composition was prepared using the polyester urethane acrylate (A1) of α1 and isobornyl acrylate (B). In this example, the polyester urethane acrylate (A2), the isocyanate compound (X) and the auxiliary agents (C, D, E, F) were not used.

[0155] (Comparative Example 3)

[0156] The polyester polyurethane acrylate (A1) of α3, the polyester polyurethane acrylate (A2) of α12, ethylene glycol diacrylate as an acrylate monomer instead of isobornyl acrylate (B), and auxiliary agents (C, D, E, F) are mixed to prepare an adhesive composition. In this example, no isocyanate compound (X) is used. It should be noted that the amount of ethylene glycol diacrylate is recorded in the column of isobornyl acrylate (B), and the mass ratio of (A1) to ethylene glycol diacrylate is recorded in the column of A1 / B.

[0157] [Production of battery packaging materials]

[0158] The first adhesive layer 12 is prepared using the adhesive composition of each example described above. Figure 1 and Figure 2 The battery packaging materials 1 and 2 have a laminated structure as shown.

[0159] Materials other than that of the first adhesive layer 12 are common and will be described below.

[0160] As the barrier layer 11 , an aluminum foil made of A8079 having a thickness of 40 μm was used.

[0161] As the heat-resistant resin layer 13 , a biaxially stretched 6-nylon film having a thickness of 15 μm was used.

[0162] As the sealant layer 15 , a 30 μm-thick unstretched polypropylene film containing 3000 ppm of erucamide was used.

[0163] As the second adhesive layer 14 , the same adhesive composition as that of the first adhesive layer 12 is used.

[0164] (Examples 1 to 15, 17, Comparative Examples 1 to 4)

[0165] A chemical conversion treatment solution containing polyacrylic acid (acrylic resin), chromium (III) salt compound, water, and alcohol was applied to both sides of the barrier layer 11, and then dried at 150° C. to form a chemical conversion film. The chromium adhesion amount of the chemical conversion film was 5 mg / m per single side. 2 The chemical conversion film is used as the base layer 16a, 16b.

[0166] The adhesive composition of each example was adjusted in viscosity using ethyl acetate so that the solid content was 25% by mass, and applied by a bar coater to a surface of the barrier layer 11 having the base layers 16a and 16b formed on both surfaces in a dry coating amount of 4.5 g / m 2 The first adhesive layer 12 was formed by volatilizing ethyl acetate in a dryer, and then a heat-resistant resin layer 13 was laminated. Furthermore, a second adhesive layer 14 with a thickness of 2 μm was formed on the other side of the barrier layer 11 in the same manner as the first adhesive layer 12, and a sealant layer 15 was laminated. Next, the laminate was sandwiched on a hot plate at 60°C. Then, both sides were irradiated with 300 mJ / cm 2 × 3 seconds of ultraviolet light, we get Figure 2 Battery packaging material 2.

[0167] (Example 16)

[0168] The layers were laminated in the same manner as in Example 1 except that the base layers 16a and 16b were not formed on the barrier layer 11 to produce Figure 1 The battery packaging material 1 has a laminated structure as shown.

[0169] [Evaluation of battery packaging materials]

[0170] The sealing resistance, hot water resistance, moist heat resistance, and high-temperature lamination strength of the produced battery packaging materials 1 and 2 were tested and evaluated by the following methods. The results are shown in Table 1.

[0171] (Sealing resistance)

[0172] Made from battery packaging materials 1 and 2 Figure 3The battery case 50 shown in the figure is subjected to a heat sealing test. The battery case 60 is formed by a molded container 51 and a flat cover plate 52. It should be noted that Figure 3 The battery case 60 of the embodiment uses the battery packaging material 1, but since the battery case using the battery packaging material 2 also has the same shape, the battery case using the battery packaging material 2 is replaced by Figure 3 .

[0173] The molded container 51 is formed by deep drawing the sheet-like battery packaging materials 1 and 2 into a roughly rectangular parallelepiped shape (a roughly rectangular parallelepiped shape with one face open) of 55 mm in length × 35 mm in width × 5 mm in depth using a deep drawing tool manufactured by AMADA Co., Ltd., and the portion extending outward from the edge of the opening of the rectangular parallelepiped is trimmed so as to leave a flange 53 of 20 mm in width. The outer surface of the molded container 51 is a heat-resistant resin layer 13, and the inner surface is a sealant layer 15. The cover plate 52 is produced by cutting the battery packaging material 1 into a rectangular shape having the same size as the outer dimensions of the flange 53 of the molded container 51. Five sets of the molded containers 51 and the cover plates 52 are prepared.

[0174] The sealant layer 15 side surface of the cover plate 52 was superposed on the molded container 51 to assemble the battery case, and the superposed flange 53 was sandwiched between heaters and heated at 70° C. for 6 seconds for heat sealing. Thus, five heat-sealed battery cases 50 were obtained.

[0175] The five heat-sealed battery cases 50 were visually observed to check for the presence of delamination in the heat-sealed portion and the presence of lifting in the appearance, and were evaluated based on the following criteria.

[0176] ◎: No delamination and no lifting of the appearance (pass)

[0177] ○: Although slight delamination sometimes occurs rarely, there is substantially no delamination and no floating in appearance (pass)

[0178] ×: Delamination occurs and there is also floating on the surface (unacceptable)

[0179] (Hot water resistance)

[0180] Five battery cases 50 prepared in the sealing resistance test were immersed in hot water at 85° C. for 240 hours, taken out, and visually inspected for delamination at the heat-sealed portion and for floating of the appearance. Evaluation was performed based on the following criteria.

[0181] ◎: No delamination and no lifting of the appearance (pass)

[0182] ○: Although slight delamination sometimes occurs rarely, there is substantially no delamination and no floating in appearance (pass)

[0183] ×: Delamination occurs and there is also floating on the surface (unacceptable)

[0184] (Moisture and heat resistance)

[0185] The sheet-like battery packaging materials 1 and 2 were deep-drawn into a substantially rectangular parallelepiped shape (a substantially rectangular parallelepiped shape with one face open) of 55 mm in length × 35 mm in width × 7 mm in depth using a deep-drawing tool manufactured by AMADA Co., Ltd. to produce a molded container 51. The molded container 51 was stored in a constant temperature and humidity chamber at a temperature of 85° C. × 85% RH for 7 days.

[0186] During the storage period, the molded container 51 was inspected after 24 hours and after 120 hours, and evaluated based on the following criteria.

[0187] ◎: No delamination after 120 hours

[0188] ○: No delamination after 24 hours, but delamination occurred after 120 hours

[0189] ×: Delamination occurred after 24 hours

[0190] (High temperature lamination strength)

[0191] A test material of 15 mm in width and 150 mm in length was cut out from the battery packaging materials 1 and 2 , and the test material was peeled off between the barrier layer 11 and the heat-resistant resin layer 13 in a region from one end in the longitudinal direction of the test material to a position 10 mm inside.

[0192] According to JIS K6854-3 (1999), a laminate including the barrier layer 11 was clamped and fixed with one chuck, and the peeled heat-resistant resin layer 13 was clamped and fixed with another chuck using a strograph (AGS-5kNX) manufactured by Shimadzu Corporation. After being kept at a temperature of 120° C. for 1 minute, the laminate was subjected to T-peeling at a tensile speed of 100 mm / min in a temperature of 120° C. to measure the peel strength at this time, and the value when the measured value stabilized was defined as "Lamination strength at high temperature (N / 15 mm)". The measurement results were evaluated based on the following criteria.

[0193] (Judgment Criteria)

[0194] ◎:2.0N / 15mm or more

[0195] ○: 1.5N / 15mm or more and less than 2.0N / 15mm

[0196] ×: Less than 1.5N / 15mm [Table 1]

[0197]

[0198] From the results in Table 1, it can be confirmed that by using the adhesive composition of the example, high high-temperature strength can be obtained and delamination can be prevented.

[0199] This application claims priority to Japanese patent application No. 2022-120392 filed on July 28, 2022, the disclosure of which directly constitutes a part of this application.

[0200] The terms and expressions used herein are used for explanation and are not to be interpreted in a limiting sense. Any equivalents of the features shown and described herein are not excluded, and various modifications are allowed within the scope of the claims of the present invention.

[0201] Industrial Applicability

[0202] The battery packaging material of the present invention can be suitably used as a casing material for secondary batteries for vehicle-mounted, stationary, notebook computers, mobile phones, and cameras, particularly for small portable lithium ion secondary batteries.

[0203] Description of Reference Numerals

[0204] 1…Battery packaging materials

[0205] 11… Barrier layer

[0206] 12…1st adhesive layer

[0207] 13…Heat-resistant resin layer

[0208] 14…Second adhesive layer

[0209] 15…Sealing agent layer

[0210] 16a, 16b…basal layer

[0211] 50…Battery housing

[0212] 60…Battery

Claims

1. A battery packaging material, wherein a heat-resistant resin layer is laminated to one surface of a barrier layer via a first adhesive layer, and a sealant layer is laminated to the other surface via a second adhesive layer, wherein: The first adhesive layer is composed of an adhesive composition containing polyester urethane acrylate (A) and a (meth)acrylate monomer having an isobornyl group (B) at a mass ratio of (A) / (B)=1 / 1 to 8 / 1.

2. The battery packaging material according to claim 1, wherein The adhesive composition comprises two or more polyester urethane acrylates (A) having different glass transition temperatures, and at least one of the polyester urethane acrylates (A) has a glass transition temperature of 40° C. or less.

3. The battery packaging material according to claim 1 or 2, wherein: The adhesive composition further includes at least one of an epoxy resin (C), a radical polymerizable compound (D) containing an alkoxysilyl group, a (meth)acrylate containing a phosphoric acid group (E), and a photocationic polymerization initiator (F).

4. The battery packaging material according to claim 1 or 2, wherein: The adhesive composition further comprises at least one of 1% to 10% by mass of an epoxy resin (C), 0.1% to 5% by mass of a free radical polymerizable compound (D) containing an alkoxysilyl group, 0.1% to 5% by mass of a (meth)acrylate containing a phosphate group (E), and 0.1% to 5% by mass of a photocationic polymerization initiator (F). 5 . The battery packaging material according to claim 1 , wherein a base layer is formed on at least the surface of the barrier layer on the heat-resistant resin layer side.

6. A battery housing, characterized in that: The battery packaging material according to claim 1 or 2 is brought together so that the sealant layers face inward and the edges are heat-sealed to form a battery element chamber for housing a battery element.

7. A secondary battery, characterized in that The battery element chamber of the battery case according to claim 6 accommodates a battery element.

Citation Information

Patent Citations

  • Treatment of organic waste water

    JP1982004298A

  • Method for installing shelf for fruit tree cultivation and jig for on-site installation used in the method

    JP2022120392A